2018
DOI: 10.1371/journal.pone.0198196
|View full text |Cite
|
Sign up to set email alerts
|

Pathological presentation of cardiac mitochondria in a rat model for chronic kidney disease

Abstract: BackgroundMitochondria hold crucial importance in organs with high energy demand especially the heart. We investigated whether chronic kidney disease (CKD), which eventually culminates in cardiorenal syndrome, could affect cardiac mitochondria and assessed the potential involvement of angiotensin II (AngII) in the process.MethodsMale Lewis rats underwent 5/6 nephrectomy allowing CKD development for eight months or for eleven weeks. Short-term CKD rats were administered with AngII receptor blocker (ARB). Cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 41 publications
(46 reference statements)
1
25
0
Order By: Relevance
“…Most studies on the impact of iv iron are limited to acute systemic oxidative effects, disregarding their longer-term impact and benefits. Despite the central role of mitochondria (within the kidney) in the possible initiation and progression of CKD [18,19,20] and the integral role of iron in key mitochondrial proteins (aconitase, complex I, II or III), the impact of parenteral iv iron therapy as employed in clinical practice on mitochondrial function, oxidative stress and CKD progression has not been sufficiently characterised.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on the impact of iv iron are limited to acute systemic oxidative effects, disregarding their longer-term impact and benefits. Despite the central role of mitochondria (within the kidney) in the possible initiation and progression of CKD [18,19,20] and the integral role of iron in key mitochondrial proteins (aconitase, complex I, II or III), the impact of parenteral iv iron therapy as employed in clinical practice on mitochondrial function, oxidative stress and CKD progression has not been sufficiently characterised.…”
Section: Introductionmentioning
confidence: 99%
“…Mar. Drugs 2021, 19, x FOR PEER REVIEW 2 of 10 mitochondrial biogenesis are related to cardiovascular disease [8,9]. Improving mitochondrial biogenesis may be beneficial for cardioprotection in CKD.…”
Section: Changes In Factors Related To Mitochondrial Biogenesis 221 Nrf1 and Nrf2 Expressionmentioning
confidence: 99%
“…Although mitochondrial biogenesis may link to pathogenesis of mitochondrial dysfunction in non-diabetic chronic kidney disease (CKD), research on this topic is also very limited. CKD and mitochondrial biogenesis are related to cardiovascular disease [ 8 , 9 ]. Improving mitochondrial biogenesis may be beneficial for cardioprotection in CKD.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondrial dysfunction is also responsible for reduction in ATP synthesis, and will add to the cellular apoptotic state [ Figure 1]. Interestingly, it has been recently reported that CKD in a rat model can influence cardiac pathologies by changing the function of cardiac tissue and inducing mitochondrial swelling and damage [90] .…”
Section: Cin Pathophysiology In the Context Of Cvdmentioning
confidence: 99%